The “Super” Traditional Dancer: Her Shared Destiny with Common Superhero - Widya Nirmalawati; Andrik Purwasito; Warto Warto; Sri Kusumo Habsari (Universitas Sanata Dharma, 2021)
Being a ronggeng dancer constitutes a turning point in a life to be at an upper level of humanity. It is similar to Superman who needs a special stone to be in his superiority, and other heroes with their specialties. A ronggeng, a Javanese traditional dancer, should be gifted with an indang spirit believed to be the dancer maker. For Srintil case, in Ronggeng Dukuh Paruk novel, she is at a much higher level compared to the others. She is the last to live in the shift of the culture. This study aimed to reveal Srintil’s superhero characteristics and what destroyed her heroism. It is a qualitative study using the heroism concept. The techniques of collecting the data were reading, note-taking, and documenting in the form of narration and dialogue taken from the novel in accordance with the research problem. The finding showed there are four criteria that made Srintil a superhero for Dukuh Paruk’s people: how she obtained a superpower; her journey to be a ronggeng; her willingness to help others; and how she sacrifices her life. However, there were men of the super culture who destroyed Srintil heroism. The indang had also prevented her from realizing her dreams, including having a true lover and having a family. Furthermore, it only left her with miseries by ended up in prison and insanity.